2019
DOI: 10.1590/1678-5150-pvb-5821
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus and Streptococcus agalactiae: prevalence, resistance to antimicrobials, and their relationship with the milk quality of dairy cattle herds in Minas Gerais state, Brazil

Abstract: Bovine mastitis is the most frequent disease worldwide in dairy herds, causing high economic losses to producers and industry, as well as having implications for public health due to the zoonotic potential of some agents involved in its etiology and the increased risk of antimicrobial residues in milk and its derivatives. Considering the multifactorial aspect of this disease, knowledge of the agents involved in its etiology and their antimicrobial susceptibility profiles is very important. This study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
2
24
2
6
Order By: Relevance
“…Beyond that, even if we excluded resistance to penicillin, as proposed by Magiorakos et al [ 10 ], 30 (15.87%) isolates were regarded as multidrug-resistant S. aureus . A high proportion of S. aureus isolates originated from IMIs harboring resistance to tetracycline and penicillin has been previously observed in Brazil [ 22 , 23 ], which corroborates our findings. Nevertheless, our study showed a high level of resistance to gentamycin in S. aureus originating from IMIs, although gentamycin resistance frequencies reported are generally low [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Beyond that, even if we excluded resistance to penicillin, as proposed by Magiorakos et al [ 10 ], 30 (15.87%) isolates were regarded as multidrug-resistant S. aureus . A high proportion of S. aureus isolates originated from IMIs harboring resistance to tetracycline and penicillin has been previously observed in Brazil [ 22 , 23 ], which corroborates our findings. Nevertheless, our study showed a high level of resistance to gentamycin in S. aureus originating from IMIs, although gentamycin resistance frequencies reported are generally low [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…A high proportion of S. aureus isolates originated from IMIs harboring resistance to tetracycline and penicillin has been previously observed in Brazil [ 22 , 23 ], which corroborates our findings. Nevertheless, our study showed a high level of resistance to gentamycin in S. aureus originating from IMIs, although gentamycin resistance frequencies reported are generally low [ 22 , 23 ]. The high level of multidrug resistant S. aureus found here, together with the predominance of an udder-adapted strain, may contribute to our knowledge of the history of the high level of mastitis caused by this pathogen, as the existence of penicillin-resistant S. aureus is related to low cure rates for S. aureus IMI treatment with either β-lactam or non-β-lactam antimicrobials [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, this contaminated food provoked a foodborne outbreak and 140 patients presented primary symptoms of sore throat and fever [ 150 ]. Bovine mastitis is the most frequent disease worldwide in dairy herds, causing high economic losses for producers and the industry, as well as having implications for public health due to the zoonotic potential of some agents involved in its etiology and the increased risk of antimicrobial residues in milk and its derivatives [ 151 ].…”
Section: Antibacterial Potential Of Bioactive Compounds From Macromentioning
confidence: 99%
“…The prevalence of S. agalactiae in 306 dairy herds from Campo das Vertentes region, located in the south of Minas Gerais state, Brazil, was evaluated. The study involved approximately 3.4 × 10 4 dairy cows and covered an area of approximately 1.2 × 10 4 km 2 and indicated that 67% of the samples were contaminated with S. agalactiae [ 151 ]. S. agalactiae was also found in bulk milk from Prince Edward Island dairy farms [ 152 ].…”
Section: Antibacterial Potential Of Bioactive Compounds From Macromentioning
confidence: 99%
“…Also, a high antimicrobial resistance to β-lactam antibiotics was identified in the MIC test.4.2 INTRODUCTIONStaphylococcus aureus is a commensal skin pathogen, capable of infecting humans, cattle and a variety of other species. This microorganism is frequently isolated from raw milk(BOUFAIDA ASNOUNE et al, 2012;SAIDI;KHELEF;KAIDI, 2013) and its within-herd prevalence on Brazilian dairy farms was reported to be 7.4%(DITTMANN et al, 2017) and of 70.3% among herds(MESQUITA et al, 2019). Intramammary infections (IMI) caused by S.…”
mentioning
confidence: 99%